Quality Perceptions of Stakeholders in Beninese Export-Oriented Shrimp Chain - Dabadé, D. Sylvain; HOUNHOUIGAN, DJIDJOHO JOSEPH; AZOKPOTA, PAULIN; DEN BESTEN, Heidy M.W.; NOUT, M.J. Robert (My University, 2014)
In recent years, the Beninese shrimp sector has faced a ban on export to the European Union due to lack of compliance with food safety standards. The present study aimed at obtaining insight into the factors that determine shrimp quality and safety in Benin. A survey was conducted to investigate the relationships between stakeholders, the conditions under which shrimps are handled at fishing areas and processed at shrimp plants, and the stakeholders’ perceptions of quality. A total of 325 fishermen, 128 intermediate traders, 12 collectors, and 3 shrimp processing plant managers were interviewed face to face. The results showed that various specific relations existed between the stakeholders. For example, loyalty was ensured by family relationships, or incentives were provided to ensure a supply of shrimps between stakeholders. Shrimp handling practices during the steps prior to shrimp processing at the plants were not in agreement with the requirements of the European regulations. For example, shrimps were kept at ambient temperature (28 ¡ 1uC) by 94.1% of fishermen and 60.9% of intermediate traders. Shrimps were also stored in inappropriate holding containers and washed with nonpotable water. Fishermen, intermediate traders, and collectors considered shrimp size and texture their priority quality attributes, whereas plant managers considered shrimp appearance (freshness) and texture their priority quality attributes. This survey demonstrated that the steps prior to shrimp processing at the plants are the critical steps for shrimp quality and safety because of temperature abuse and inappropriate hygienic conditions. There is a need to communicate and provide incentives for the stakeholders in the first part of the chain to give priority to shrimp freshness. Moreover, training in Good Fishing Practices and safe food handling practices and evaluation of compliance with the practices through monitoring will contribute to better shrimp quality and safety management.
Keywords: Shrimp; Benin; Quality